2017
DOI: 10.3732/ajb.1600276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil type and light on height growth, biomass partitioning, and nitrogen dynamics on 22 species of tropical dry forest tree seedlings: Comparisons between legumes and nonlegumes

Abstract: Legumes may have a different regeneration niche, in that they germinate rapidly and grow taller than other species immediately after germination, maximizing their performance when light and belowground resources are readily available, and potentially permitting them to take advantage of high light, nutrient, and water availability at the beginning of the wet season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…In a shade house experiment conducted in the same region and with some of the same species, Smith‐Martin et al . () found that under lower light intensities seedlings allocated more biomass to leaves, whereas under higher light intensities they allocated more to roots. Thus, juveniles may need to be more flexible in their allocation patterns to be able to respond to the environment and dynamically allocate more biomass depending on whether above‐ vs belowground resource availability is scarcest.…”
Section: Discussionmentioning
confidence: 97%
“…In a shade house experiment conducted in the same region and with some of the same species, Smith‐Martin et al . () found that under lower light intensities seedlings allocated more biomass to leaves, whereas under higher light intensities they allocated more to roots. Thus, juveniles may need to be more flexible in their allocation patterns to be able to respond to the environment and dynamically allocate more biomass depending on whether above‐ vs belowground resource availability is scarcest.…”
Section: Discussionmentioning
confidence: 97%
“…To link functional trait data with tree species occurring in the plots, we used previously published databases of functional traits (Powers & Tiffin, ), seed mass (Smith‐Martin et al, ) and wood anatomy traits (Werden, Waring, Smith‐Martin, & Powers, ) all collected in the same region using standard methods (Pérez‐Harguindeguy et al, ). From (Powers & Tiffin, ), we collated mean species‐level values of specific leaf area (SLA; cm 2 /g), leaf area (cm 2 ), leaf dry matter content (LDMC; g/g), wood density (g/cm 3 ), foliar δ 13 C (‰), foliar phosphorus (P; %), nitrogen (N; %) and carbon (C; %), leaf type (simple or compound) and habit (deciduous, semi‐deciduous and evergreen).…”
Section: Methodsmentioning
confidence: 99%
“…From (Powers & Tiffin, ), we collated mean species‐level values of specific leaf area (SLA; cm 2 /g), leaf area (cm 2 ), leaf dry matter content (LDMC; g/g), wood density (g/cm 3 ), foliar δ 13 C (‰), foliar phosphorus (P; %), nitrogen (N; %) and carbon (C; %), leaf type (simple or compound) and habit (deciduous, semi‐deciduous and evergreen). Additional trait data were gathered for mean seed mass (g; Smith‐Martin et al, ), maximum adult tree height (m; J.S. Powers, unpublished), wood vessel diameter (mm) and xylem vessel density (# vessels/cm 3 ; Werden, Waring, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…All rights reserved 2018). New findings from ACG show that the success of legumes may be attributed to their rapid germination rates coupled with higher seedling growth rates (Vargas et al 2015;Smith-Martin et al 2017), or their distinct functional traits such as high leaf carbon and nitrogen (Powers and Tiffin 2010) and their ability to fix nitrogen. Another example of plant species that have been extensively studied in ACG is Quercus oleoides Cham.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…5; Vargas et al 2018). Other experiments are testing for local adaptation to water availability using reciprocal transplant and germination experiments in Quercus oleoides (Center et al 2016; Ramirez-Valiente and Cavendar-Bares 2017) as well as other common dry forest species (Vargas et al 2015;Smith-Martin et al 2017). In addition, high resolution down-scaled climate models are becoming increasingly available for ACG (Ugalde Gómez et al 2009;Alvarado et al 2012; Durán In Review) and will aid predictive models of forest dynamics (Xu et al 2016).…”
Section: The Importance Of Local and Global Collaborations For The Fumentioning
confidence: 99%